Pengaruh Fasilitas Wisata, Persepsi Harga dan Citra Destinasi terhadap Minat Berkunjung Kembali dengan Kepuasan Sebagai Variabel Mediasi: (Studi Pada Pengunjung Wisata Alam Bukit Aslan Bandar Lampung) - Sofi Apriliani; Vitria Susanti; Nurhayati Nurhayati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to identify factors that influence tourists' interest in revisiting the Aslan Hill natural tourist attraction. The methodology used is to use a quantitative approach with data obtained from the results of questionnaires that have been distributed to the sample (research respondents) totaling 96 people. Through quantitative analysis with the help of Smart PLS software. 4, this study found that although the three independent variables (tourism facilities, price perception, and destination image) had a positive relationship with revisit intention, only price perception and destination image had a statistically significant influence. Apart from that, this research also confirms that the mediating variable is visitor satisfaction in the relationship between price perception and destination image and interest in visiting again, where satisfaction cannot mediate the influence of tourist facilities on interest in visiting again, while satisfaction can mediate the relationship between price perception and destination image on interest in visiting. return to the Aslan Hill Nature tourist attraction. The practical implication of this research is that it is important for natural tourism destination managers to not only focus on developing physical facilities, but also on efforts to build positive perceptions about the value offered and maintain consistent service quality to achieve visitor satisfaction.